Guru Kristen sebagai Pembimbing dan Penuntun dalam Konsep Kelas Tiga Dinding Ki Hajar Dewantara Melalui Pembelajaran Autentik [The Christian Teacher as Mentor and Guide in Ki Hajar Dewantara's Third Wall Classroom Concept Through Authentic Learning] - Sihombing, Sarali; Rahmadi, Pitaya (Diligentia: Journal of Theology and Christian Education, 2024)
The Christian teacher as guide and mentor is not focused on academic achievement only, but rather guides and assists students to become like Christ and responsible individuals. However, the reality is that many teachers still adopt traditional learning, neglect other skills, and distance themselves from Biblical truth. This article presents the role of the Christian teacher as a guide and mentor in the context of the relevance of science to the environment, especially Ki Hajar Dewantara's "Three Wall Classroom" concept through authentic learning based on biblical insights using a literature review. As a result, Christian teachers as mentors and guides are able to create holistic learning, meaningful and relevant learning, collaborate with reality, and bring students to the knowledge of God. In conclusion, the Christian teacher as a guide and mentor in the "Three Walls Classroom" through authentic learning is to center learning on Christ, motivate student development in all aspects, and become an agent of restoring students' relationship with God. As a suggestion, a teacher must understand the calling as a ministry. For future writers, it is suggested to dig deeper into educational issues and add relevant evidence or data.BAHASA INDONESIA ABSTRACT: Guru Kristen sebagai pembimbing dan penuntun bukanlah guru yang berfokus pada pencapaian akademik, melainkan membimbing dan mendampingi siswa serupa dengan Kristus dan menjadi pribadi yang bertanggung jawab. Namun, realitanya banyak guru masih mengadopsi pembelajaran tradisional, mengabaikan keterampilan lain, dan memberi jarak dengan kebenaran Alkitab. Karya tulis ini memaparkan peran guru Kristen sebagai pembimbing dan penuntun dalam konteks relevansi ilmu pengetahuan dengan lingkungan terkhusus konsep "Kelas Tiga Dinding" Ki Hajar Dewantara melalui pembelajaran autentik berlandaskan wawasan Alkitabiah menggunakan kajian literatur. Hasilnya, guru Kristen sebagai pembimbing dan penuntun mampu menciptakan pembelajaran holistis, pembelajaran bermakna dan relevan, berkolaborasi dengan realita, dan membawa siswa kepada pengenalan akan Allah. Kesimpulannya, guru Kristen sebagai pembimbing dan penuntun dalam Kelas Tiga Dinding melalui pembelajaran autentik adalah memusatkan pembelajaran pada Kristus, memotivasi perkembangan siswa dalam segala aspek, dan menjadi agen pemulihan hubungan siswa dengan Allah. Sebagai saran, seorang guru harus memahami panggilannya sebagai suatu pelayanan. Bagi penulis selanjutnya, disarankan menggali lebih dalam isu pendidikan dan menambah bukti atau data relevan.